Mª Lourdes REDONDO, Alpinistas del espíritu. Pablo VI y los institutos seculares, Madrid: FUE, 2022, 208 pp., 15 x 20, ISBN 978-84-1967-200-1. - Pro-Velasco, María-Luisa (Scripta Theologica, 2023)
Book Review